Parasitoids of Bactrocera oleae (Gmelin.) (Diptera: Tephritidae) infesting the fruits of Olea eurapea var. sylvestris Brat. in Sicily (Bollettino di zoologia agraria e bachicoltura, 2024)
Data concerning the parasitism observed in Sicily, during the years 2002 and 2003, on larvae and pupae of Bactrocera oleae (Gmelin) (Diptera: Tephritidae) infesting the fruits of Olea europea var. sylvestris Brat. are reported. An average of 7500 and 19800 fruits were examined in the two years, respectively. The parasitoids emerged were: Opius concolor (Szepligeti) (Braconidae); Asecodes erxias (Walker) and Pnigalio agraules (Walk.) (Eulophidae); Eupelmus urozonus Dalm. (Eupelmidae) and Hobbya sp. (Pteramalidae). In the year 2002 the total parasitism registered was 47.30%, while 49.80% on 2003. The highest percentage was due to P. agraules, i.e 37.02% and 43.14%, respectively; it was followed by O. concolor with 10.04% on 2002 and 6.0% about on 2003. Only some adults were accounted of the other parasitoids in the two years.
Keywords: Bactrocera oleae; biological control